2016
DOI: 10.1542/peds.2016-0922
|View full text |Cite
|
Sign up to set email alerts
|

The Female Athlete Triad

Abstract: The number of girls participating in sports has increased significantly since the introduction of Title XI in 1972. As a result, more girls have been able to experience the social, educational, and health-related benefits of sports participation. However, there are risks associated with sports participation, including the female athlete triad. The triad was originally recognized as the interrelationship of amenorrhea, osteoporosis, and disordered eating, but our understanding has evolved to recognize that each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 74 publications
0
32
0
2
Order By: Relevance
“…Examples of intrinsic factors include metabolic bone diseases and nutritional or hormonal deficiencies. In particular, young female athletes with a low BMI and history of amenorrhea are at increased risk for stress fractures and should be screened for possible female athlete triad (11). Extrinsic factors include type of sport, training surface, shoe wear, and most commonly a sudden increase in training regimen (12).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of intrinsic factors include metabolic bone diseases and nutritional or hormonal deficiencies. In particular, young female athletes with a low BMI and history of amenorrhea are at increased risk for stress fractures and should be screened for possible female athlete triad (11). Extrinsic factors include type of sport, training surface, shoe wear, and most commonly a sudden increase in training regimen (12).…”
Section: Discussionmentioning
confidence: 99%
“…The questions in this survey were derived from athlete screening during previous research trials and included questions from the Female Athlete Triad Screening Questionnaire, Triad Consensus Panel Screening Questionnaire, Athlete Sleep Screening Questionnaire, and the Recovery Stress Questionnaire for Athletes. 7 , 4 , 9 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…When examined by sport, bones of the lower extremities and lumbar vertebrae show high values at the load sites in volleyball and weight lifting players, whereas competitive swimmers show lower bone density compared with athletes who play other sports with a lack of load . It has been reported that non‐athletes with oligomenorrhea or amenorrhea have low BMD compared with those with eumenorrhea . However, bone density has not been shown to be low in gymnasts with amenorrhea compared with those with eumenorrhea.…”
Section: Factors Composing Fatmentioning
confidence: 99%